Religion in the public sphere: a contested field in late modern societies = La religión en la esfera pública : un campo controvertido en las sociedades modernas tardías = Religião na esfera pública : um campo contestado nas sociedades modernas - Grümme, Bernhard (Teocomunicação, 2021)
Religion has become a highly ambivalent phenomenon in late modernity. For some, it is a lasting resource for meaning, even in a highly ideologically plural society. For others, it belongs in the private sphere, not in the public sphere. What both would probably share, however, is the assumption that a state religion would be in contradiction to the promises of freedom and autonomy of modernity. But where is the place of religion in a democratic society? The text discusses this highly complex question in an examination of two theories that have shaped debates in the field like few others. From this discussion, further perspectives for a theologically founded position that is responsible in terms of democratic theory are given in conclusion.